2014
DOI: 10.3389/fnhum.2014.00641
|View full text |Cite
|
Sign up to set email alerts
|

A new perspective on binaural integration using response time methodology: super capacity revealed in conditions of binaural masking release

Abstract: This study applied reaction-time based methods to assess the workload capacity of binaural integration by comparing reaction time (RT) distributions for monaural and binaural tone-in-noise detection tasks. In the diotic contexts, an identical tone + noise stimulus was presented to each ear. In the dichotic contexts, an identical noise was presented to each ear, but the tone was presented to one of the ears 180° out of phase with respect to the other ear. Accuracy-based measurements have demonstrated a much low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…Because ensemble coding allows observers to generate an efficient representation of a set by extracting information from multiple items in parallel, larger sets may provide more information on which to base the average and thus improve the efficiency of ensemble perception. Our finding is in line with the suggestion by Alvarez (2011) that displays with more items result in a higher signal-to-noise ratio (SNR), and reports that auditory stimuli with higher SNR are associated with faster RTs (Lentz, He, & Townsend, 2014).…”
Section: Discussionsupporting
confidence: 93%
“…Because ensemble coding allows observers to generate an efficient representation of a set by extracting information from multiple items in parallel, larger sets may provide more information on which to base the average and thus improve the efficiency of ensemble perception. Our finding is in line with the suggestion by Alvarez (2011) that displays with more items result in a higher signal-to-noise ratio (SNR), and reports that auditory stimuli with higher SNR are associated with faster RTs (Lentz, He, & Townsend, 2014).…”
Section: Discussionsupporting
confidence: 93%
“…Finally, loudness is increased by binaural summation. Numerous studies have shown that RT to the onset of a tone presented to both ears is slightly shorter than to a tone presented to one ear only (Chocholle, 1944;Lentz et al, 2014;Schröter et al, 2007;Simon, 1967) and that the level difference needed to obtain equal RT comes close to the one required for equal loudness (Schlittenlacher et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Binaural beats are an auditory processing artefact created by the interference between two similar frequencies of sound presented to each ear via earphones [ 22 , 23 ]. Disparate audible tones of up to 1000 hertz (Hz) frequency, differing by less than approximately 30 Hz, are processed by the brain via binaural integration, allowing perception of a third, subliminal tone [ 24 , 25 ]. The frequency of this illusory tone is equal to the mean frequency of the two stimuli, while its amplitude fluctuates with a frequency amounting to the difference between the stimuli [ 26 ].…”
Section: Introductionmentioning
confidence: 99%